RUWAT PANJI AT THE KRUCIL PUPPET SHOW - Irawanto, Rudi (International Conference on Cultural Studies, 2019)
Ruwat for the Javanese community, is interpreted as a process of self-liberation from bad elements. The bad elements are the caused by Heredity, actions that have been carried out or from a bad environment. Liberation in the ruwat procession can be done with certain media, usually using puppets, offerings and spells that are read by the mastermind. In the process of ruwat Panji , the implementation of ruwat became a series of Semirang Panji stories. The core story of ruwat Panji is the process of liberating the goddess Sekartaji in Panji Semirang's body.The process of Panji Semirang's liberation of the body is not seen solely as an attempt to cleanse himself as in general, but can be interpreted as an Affirmation of the body's function in the perception of the Javanese community. The body in the perception of the Javanese is only a place ( wadag ) that can be changed in its functions and roles. The individual's position is not in the presence of his body but in the character inherent in him. The body IS ALSO A representation of the Macrocosm, the which in it is always associated with the essence of Godhead.The Panji ruwat procession indicates that the body can be exchanged, changed and even eliminated its physical essence. The body is an imperfect form, so it needs to be perfected. Perfecting the existence of the body can only be done by the way of union with God. The process of ruwatPanji is a representation of Javanese society's view of the body and its relationship with the essence of God. s position is not in the presence of his body but in the character inherent in him. The body IS ALSO A representation of the Macrocosm, the which in it is always associated with the essence of Godhead.The Panji ruwat procession indicates that the body can be exchanged, changed and even eliminated its physical essence. The body is an imperfect form, so it needs to be perfected. Perfecting the existence of the body can only be done by the way of union with God. The process of ruwat Panji is a representation of Javanese society's view of the body and its relationship with the essence of God. s position is not in the presence of his body but in the character inherent in him. The body IS ALSO A representation of the Macrocosm, the which in it is always associated with the essence of Godhead.The Panji ruwat procession indicates that the body can be exchanged, changed and even eliminated its physical essence. The body is an imperfect form, so it needs to be perfected. Perfecting the existence of the body can only be done by the way of union with God. The process of ruwat Panji is a representation of Javanese society's view of the body and its relationship with the essence of God. The body is an imperfect form, so it needs to be perfected. Perfecting the existence of the body can only be done by the way of union with God. The process of ruwat Panji is a representation of Javanese society's view of the body and its relationship with the essence of God. The body is an imperfect form, so it needs to be perfected. Perfecting the existence of the body can only be done by the way of union with God. The process of ruwat Panji is a representation of Javanese society's view of the body and its relationship with the essence of God.